Negative regulation of lymphangiogenesis by Tenascin-C delays the resolution of inflammation - Daisuke Katoh; Yoshiyuki Senga; Kento Mizutani; Kazuaki Maruyama; Daishi Yamakawa; Tadashi Yamamuro; Michiaki Hiroe; Keiichi Yamanaka; Akihiro Sudo; Naoyuki Katayama; Toshimichi Yoshida; Kyoko Imanaka-Yoshida (iScience)
Summary: Lymphatic vessels are required for the clearance of excess fluid and immune cells from inflamed tissue, making the regulation of lymphangiogenesis an important area of research. Although the positive regulatory mechanisms of lymphangiogenesis are well known, the negative regulatory mechanisms observed during inflammation remain unclear. Here, we identify tenascin-C (TNC) as a spatiotemporal negative regulator of lymphangiogenesis during inflammation. We found an inverse correlation between lymphangiogenesis and TNC expression in a mouse lymphedema model. Genetic deletion of Tnc promotes lymphangiogenesis and improves lymphatic drainage function, thereby accelerating the resolution of inflammation. Conversely, the exogenous addition of TNC suppresses lymphangiogenesis and prolongs inflammation. TNC inhibits the proliferation and promotes apoptosis of lymphatic endothelial cells. Mechanistically, TNC facilitates integrin αvβ1 heterodimer formation, leading to the activation of non-canonical (TAK1/p38MAPK/ATF-2) TGFβ signaling to suppress lymphangiogenesis. Our study highlights the importance of negative regulation of lymphangiogenesis in modulating immune responses.